Remaking Columbine - Johannes Walter Vith (Journal of the Austrian Association for American Studies, 2020)
High school shootings in the United States generally receive enormous amounts of journalistic coverage and thus spark a lot of public interest. However, the topic appears to be taboo for mainstream cinema, and there are barely any films about real-life school shootings. This article seeks to show that Gus Van Sant's Elephant (2003) is both an enlightening exception to this seeming contradiction and an interesting response to the popular narratives surrounding the Columbine High School shooting of 1999. The film is not only unique in its portrayal of a real-life school shooting but also in the way that it approaches the topic. There are three important processes that make this depiction of the Columbine High School shooting so powerful: remaking, remediating, and reflecting. First, Van Sant's film is a remake of Alan Clarke's 1989 film of the same name. Clarke's film depicts several incidents of gun violence in Northern Ireland without any commentary, and Van Sant employs the same techniques in his film about gun violence at a school. Second, the film critiques the discourse around the shooting, as it remediates video games for its filmic rhetoric. Lastly, Gus Van Sant de-narrativizes the shooting and creates a reflective space for the audience. These three aspects all influence the film's storytelling and cinematography, which aim at promoting reflection rather than providing a straightforward narrative.